Actinomycete-Derived Pigments: A Path Toward Sustainable Industrial Colorants - Blanca Hey Díez; Cristiana A. V. Torres; Susana P. Gaudêncio (Marine Drugs)
Pigment production has a substantial negative impact on the environment, since mining for natural pigments causes ecosystem degradation, while synthetic pigments, derived from petrochemicals, generate toxic by-products that accumulate and persist in aquatic systems due to their resistance to biodegradation. Despite these challenges, pigments remain essential across numerous industries, including the cosmetic, textile, food, automotive, paints and coatings, plastics, and packaging industries. In response to growing consumer demand for sustainable options, there is increasing interest in eco-friendly alternatives, particularly bio-based pigments derived from algae, fungi, and actinomycetes. This shift is largely driven by consumer demand for sustainable options. For bio-pigments, actinomycetes, particularly from the Streptomyces genus, have emerged as a promising green source, aligning with global sustainability goals due to their renewability and biodegradability. Scale-up of production and yield optimization challenges have been circumvented with the aid of biotechnology advancements, including genetic engineering and innovative fermentation and extraction methods, which have enhanced these bio-pigments’ viability and cost-competitiveness. Actinomycete-derived pigments have successfully transitioned from laboratory research to commercialization, showcasing their potential as sustainable and eco-friendly alternatives to synthetic dyes. With the global pigment market valued at approximately USD 24.28 billion in 2023, which is projected to reach USD 36.58 billion by 2030, the economic potential for actinomycete pigments is extensive. This review explores the environmental advantages of actinomycete pigments, their role in modern industry, and the regulatory and commercialization challenges they face, highlighting the importance of these pigments as promising solutions to reduce our reliance on conventional toxic pigments. The successful commercialization of actinomycete pigments can drive an industry-wide transition to environmentally responsible alternatives, offering substantial benefits for human health, safety, and environmental sustainability.